Social competence of 3 to 5-year-old children born with low birth weight - Nurul Komariah (Paediatrica Indonesiana, 2015)
Background Low birth weight (LBW) has long been used as an indicator of public health. Low birth weight is not a proxy for any dimension of other maternal or perinatal health outcomes. Low birth weight infants require special care, and have more chronic conditions, learning delays, and attention deficit hyperactivity disorders compared to infants of normal birth weight (NBW). Social competence is viewed as a primary component of healthy function and development and is an important predictor of academic and financial success.Objective To examine social competence of children aged 3-5 years born with low birth weight.Methods This cross-sectional study was undertaken in Palembang in 2012. Subjects consisted of children aged 3-5 years attended a preschool in the Seberang Ulu I District, Palembang, and were divided into two groups: low birth weight (LBW) and normal birth weight (NBW). Social competence was assessed by observation and Interaction Rating Scale (IRS) and Parenting Style questionnaire (PSQ). Chi-square analysis was used to compare social competence between the two groups. Multivariate regression logistic analysis was used to assess for the dominant factors that may affect a child’s social competence.Results Low birth weight children aged 3 to 5 years had a 1.435 times higher risk of low social competence compared to normal birth weight children of similar age. (RP 1.435; 95%CI 1.372 to 13.507; P=0.019). Multivariate regression logistic analysis revealed that parenting style was a dominant factor affecting social competence.Conclusion Social competence in 3 to 5-year-old children born with low birth weight is lower compared to those with normal birth weight.